Canva-Assisted Project Based Learning Digital Worksheet to Enhance Critical Thinking Skills in Elementary School - Damayana, Rosidah; Anggoro, Subuh; Fazilla, Sarah (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2025)
This study develops and evaluates a Canva-assisted Project Based Learning (PjBL) digital worksheet (LKPD) for food chain instruction in 5th-grade elementary students, using the ADDIE Research and Development model with a convergent mixed-method approach. A quasi-experimental pretest-posttest control group design involved 27 students in the experimental group (UPTD SDN 2 Way Mili) and 21 in the control group (UPTD SDN 3 Way Mili), selected through purposive sampling based on comparable baseline characteristics and infrastructure. Data were collected via expert validation sheets, critical thinking tests (10 essay items; validity 0.412-0.789; reliability 0.856), collaboration observation sheets, and response questionnaires, and analyzed using V-Aiken, descriptive statistics, Paired and Independent Sample T-Tests, and N-Gain Score. The digital worksheet achieved very valid status (V-Aiken = 0.90, 90.4%) and was rated very practical by students (93.4%) and teachers (4.59/5.00). The experimental group demonstrated significantly higher critical thinking gains (N-Gain = 0.78, high category) compared to the control group (N-Gain = 0.35, medium category), with statistically significant inter-group differences (t = 8.73; p < 0.001). These findings confirm that the integration of PjBL syntax with Canva’s interactive features effectively develops higher-order thinking skills aligned with 21st-century learning competencies.